MS-Excel design tool for beam column design for multistory buildings with teaching features - Chong, Weng Soon (2015)
In 2013, Eurocode was introduced by Building& Construction Authority (BCA) to replace the British Standard (BS) code. As to ensure a smooth transition of the prescribed structural design code, the industry was given two years to adapt the change. By 1st April 2015, the structural plan submission must be done in Eurocode. On the other hand, there is a rising trend of using steel for building construction, mainly due to its advantage of higher productivity over conventional reinforced concrete work. In order to meet this rising trend and statutory requirement, a simple and effective steel design tool is greatly needed. This project utilizes the Microsoft Excel and Visual Basic Aid (VBA) as the design platform for the multistory steel column design. It offers simple and user-friendly layout that will enable to have a quick check on the selected section for column design. With the aid of the macro, it will help the user to design steel column for multistory building with different loadings condition and offer more pleasant user experience as compared to the mundane design program. Another feature of this program is the function of recommending suitable section for the user, this will enable user to select a suitable section faster without having go through the trial and error method to obtain the optimal section. In addition, in calculation details page, the combined verification factor is divided to three parts of the resistance, in percentage form, to let the user have an insight to how efficient is the selected section utilize. The calculation details and the check of the section is done in accordance to EC3.Method 2 or known as Annex B and Method 1 or known as Annex A checks are presented in this program as to let user have a more stringent verification on the selected section. In addition, the calculation details are shown in a systematic and neat manner as to provide a better user experience. Lastly, this report is organized in sequence, from the theoretical basis of column design to development of this program, followed by the calculation details with example. Before ending, the author would like to inspire the future researchers or students through this program to further explore and add in value to this program.